The Effect of Thidiazuron Treatment on the Growth of Vanda limbata Blume in vivo - Ditasya Putri, Novika; Setiari, Nintya; Nurchayati, Yulita; Agung Suedy, Sri Widodo (UI Scholars Hub, 2024)
Vanda limbata is one of the most popular ornamental orchids. Currently, its growth is slow, making it necessary to improve its cultivation techniques. One of the possible ways to achieve this is to use plant growth regulator (PGR) treatment. Thidiazuron (TDZ) is a cytokinin used to increase the growth of V. limbata. This study aimed to determine the effect of TDZ concentration on the growth rate of V. limbata. The study involved cultivating V. limbata on planting media and spraying it with TDZ at various concentrations. This research uses a CRD (Completely Randomized Design) single-factor, which is TDZ concentration at three concentrations (factor levels) of 0, 25, and 50 ppm. Data were analyzed using analysis of variance and Duncan’s Multiple Range Test at 5% significance level. The study ran for three months and the following response variables were measure: the number of new leaves, increase in length of old leaves, length of new leaves, increase in width of old leaves, width of new leaves, number of roots, and stomatal density. The results showed that TDZ significantly increased leaf length and the number of new leaves of V. limbata, but decreased the density of stomata. Thidiazuron at 50 ppm was the best treatment for increasing the growth of V. limbata.